The Effect of Improvisational Behavior on Sales Performance, Mediated by Product Knowledge, Adaptive Selling Behavior, and Challenge Orientation - Fajar Soefany; Putu Nina Madiawati; R. Amalina Dewi Kumalasari; Rd. Nurafni Rubiyanti; Arry Widodo (International Journal Labs, 2026)
The increasing competition in the premium decorative paint industry requires salespeople to possess adaptive capabilities beyond technical knowledge to achieve sustainable sales performance. In dynamic market environments, improvisational behavior becomes an important capability that enables salespeople to respond creatively to unexpected customer demands and complex selling situations. This study aims to examine the effect of improvisational behavior on sales performance by investigating the mediating roles of product knowledge, adaptive selling behavior, and challenge orientation among salespeople of PT Cat X in the Sumatera Region. A quantitative explanatory research design was employed using a cross-sectional survey approach. The study involved 57 salespeople selected through a census sampling technique. Data were collected using a five-point Likert scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that improvisational behavior significantly influences product knowledge, adaptive selling behavior, and challenge orientation. However, product knowledge and adaptive selling behavior do not have significant direct effects on sales performance. Conversely, challenge orientation significantly affects sales performance and serves as a significant mediator in the relationship between improvisational behavior and sales performance. The structural model explains 67.5% of the variance in sales performance. These findings highlight that motivational transformation through challenge orientation is a key mechanism linking improvisational capability to salesperson effectiveness. Therefore, organizations should prioritize challenge-oriented development programs to enhance sales performance in competitive markets.